Variation in Nectar Volume and Sugar Concentration of Allium ursinum L. ssp. ucrainicum in Three Habitats - Ágnes Farkas; Réka Molnár; Tamás Morschhauser; István Hahn (The Scientific World Journal)
Floral nectar volume and concentration of ramson (Allium ursinum L. ssp. ucrainicum) were investigated in three different habitats, including two types of sessile oak-hornbeam association on brown forest soil with clay illuviation and a silver lime-flowering ash rock forest association on rendzina. Daily nectar production ranged from 0.1 to 3.8 μL per flower with sugar concentrations of 25 to 50%. Mean nectar volumes and concentrations showed significant differences between freely exposed flowers and covered flowers, which had been isolated from flower visitors 24 h prior to nectar studies. Both the amount and quality of nectar were affected by microclimatic conditions and soil properties and varied between populations at different habitats. In the silver lime-flowering ash rock-forest association mean nectar volumes and concentrations were lower than in a typical sessile oak-hornbeam association on three occasions, the difference being significant in two cases. During full bloom, the date of sampling did not have a profound effect on either nectar volume or concentration.